Olmutinib (BI1482694/HM61713), a Novel Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor, Reverses ABCG2-Mediated Multidrug Resistance in Cancer Cells - Zhang, Wei; Fan, Ying-Fang; Cai, Chao-Yun; Wang, Jing-Quan; Teng, Qiu-Xu; Lei, Zi-Ning; Zeng, Leli; Gupta, Pranav; Chen, Zhe-Sheng (Frontiers in Pharmacology, 2018)
The main characteristic of tumor cell resistance is multidrug resistance (MDR). MDR is the main cause of the decline in clinical efficacy of chemotherapeutic drugs. Presently, there are several mechanisms that could cause MDR. Among these, one of the most important mechanisms underlying MDR is the overexpression of the adenosine triphosphate (ATP)-binding cassette (ABC) super-family of transporters, which effectively pump out cytotoxic agents and targeted anticancer drugs across the cell membrane. In recent years, studies found that ABC transporters and tyrosine kinase inhibitors (TKIs) interact with each other. TKIs may behave as substrates or inhibitors depending on the expression of speciﬁc pumps, drug concentration, their afﬁnity for the transporters and types of co-administered agents. Therefore, we performed in-vitro experiments to observe whether olmutinib could reverse MDR in cancer cells overexpressing ABCB1, ABCG2 or ABCC1 transporters. The results showed that olmutinib at 3 μM significantly reversed drug resistance mediated by ABCG2, but not by ABCB1 and ABCC1, doing so by antagonizing the drug efﬂux function in ABCG2-overexpressing cell lines. In addition, olmutinib at reversal concentration affected neither the protein expression level nor the localization of ABCG2. The results observed from the accumulation/efflux study of olmutinib showed that olmutinib reversed ABCG2-mediated MDR with an increasing intracellular drug accumulation due to inhibited drug efflux. We also had consistent results with the ATPase assay that olmutinib stimulated ATPase activity of ABCG2 up to 3.5-fold. Additionally, the molecular interaction between olmutinib and ABCG2 was identified by docking simulation. Olmutinib not only interacts directly with ABCG2 but also works as a competitive inhibitor of the transport protein. In conclusion, the reversal effect of olmutinib on ABCG2 on MDR cells is not due to ABCG2 expression or intracellular localization, but rather related to its interaction with the ABCG2 protein resulting in drug efflux inhibition and ATPase stimulation.